2017
DOI: 10.1016/j.ijdevneu.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cerebral palsy‐like model in rats: Analysis of gait pattern and of brain and spinal cord motor areas

Abstract: In an attempt to propose an animal model that reproduces in rats the phenotype of cerebral palsy, this study evaluated the effects of maternal exposure to bacterial endotoxin associated with perinatal asphyxia and sensorimotor restriction on gait pattern, brain and spinal cord morphology. Two experimental groups were used: Control Group (CTG) − offspring of rats injected with saline during pregnancy and Cerebral Palsy Group (CPG) − offspring of rats injected with lipopolysaccharide during pregnancy, submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Subdivided driving control technology is also called micro-step control technology. The essence of this technology is to input step-by-step change direction current into the winding of the stepping motor, so that the step angle can be reduced when each step rotates, thereby improving the resolution of the motor [6][7][8]. The subdivided driving control technology reduces the step angle of each step of the motor, improves the inherent resolution of the motor, and has a good restraining effect on the low frequency oscillation, step loss, and large noise that are common in most motors.…”
Section: Subdivided Driving Technologymentioning
confidence: 99%
“…Subdivided driving control technology is also called micro-step control technology. The essence of this technology is to input step-by-step change direction current into the winding of the stepping motor, so that the step angle can be reduced when each step rotates, thereby improving the resolution of the motor [6][7][8]. The subdivided driving control technology reduces the step angle of each step of the motor, improves the inherent resolution of the motor, and has a good restraining effect on the low frequency oscillation, step loss, and large noise that are common in most motors.…”
Section: Subdivided Driving Technologymentioning
confidence: 99%
“…Animal models of SR usually try to mimic the immobility imposed by spasticity and has been already shown to be a valuable model to understand underlying mechanisms of neural adaptations occurred in response to immobility. A series of studies using the SR procedure showed that SR impact proprioceptive feedback from the hind limbs during development and affects cortical structural and functional organization ( Coq et al, 2008 ; dos Santos et al, 2017 ; Marcuzzo et al, 2010 ; Strata et al, 2004 ). Although central effects of disuse are evident, the functional impairment in motor tasks could be resulted by the combination of both central and peripheral factors.…”
Section: Introductionmentioning
confidence: 99%